Synergistic Effects of Curcumin and Piperine as Potent Acetylcholine and Amyloidogenic Inhibitors With Significant Neuroprotective Activity in SH-SY5Y Cells via Computational Molecular Modeling and in vitro Assay - Abdul Manap, Aimi Syamima; Wei Tan, Amelia Cheng; Leong, Weng Hhin; Yin Chia, Adeline Yoke; Vijayabalan, Shantini; Arya, Aditya; Wong, Eng Hwa; Rizwan, Farzana; Bindal, Umesh; Koshy, Shajan; Madhavan, Priya (Frontiers in Aging Neuroscience, 2019)
Hallmarks of Alzheimer’s disease (AD) pathology include acetylcholine deficiency and plaque deposition. Emerging studies suggest that acetylcholinesterase (AChE) may interact with amyloid beta (Aβ) to promote aggregation of insoluble amyloid beta plaques in brains of patients. Current therapeutic options available for AD patients, such as AChE inhibitors, provide only symptomatic relief. In this study, we screened four natural compounds believed to harbour cognitive benefits- curcumin, piperine, bacoside A and chebulinic acid. In the first section, preliminary screening through computational molecular docking simulations gauged the suitability of the compounds as novel AChE inhibitors. From here, only compounds that met the in silico selection criteria were selected for the second section through in vitro investigations, including AChE enzyme inhibition assay, MTT assay, ThT assay and biochemical analysis via a neuronal cell line model. Of the four compounds screened, only curcumin (-9.6kcal/mol) and piperine (-10.5kcal/mol) showed favorable binding affinities and interactions towards AChE and were hence selected. In vitro AChE inhibition demonstrated that combination of curcumin and piperine showed greater AChE inhibition with an IC50 of 62.81 ± 0.01μg/mL as compared to individual compounds, i.e., IC50 of curcumin at 134.5 ± 0.06µg/mL and IC50 of piperine at 76.6 ± 0.08µg/mL. In SH-SY5Y cell model, this combination preserved cell viability up to 85%, indicating that the compounds protect against Aβ-induced neuronal damage (p<0.01). Interestingly, our results also showed that curcumin and piperine achieved a synergistic effect at 35µM with SQ value of 1.824. Synergistic behavior indicates that combination of these two compounds at lower concentrations may provide a better outcome than individually for Aβ proteins. Combined curcumin and piperine managed to inhibit aggregation (reduced ThT intensity at 0.432a.u) (p<0.01) as well as disaggregation (reduced ThT intensity at 0.532a.u) (p<0.01) of fibrillar Aβ42. Furthermore, combined curcumin and piperine reversed the Aβ-induced up-regulation of neuronal oxidative stress (p<0.01). In conclusion, curcumin and piperine demonstrated promising neuroprotective effects whereas bacoside A and chebulinic acid may not be suitable lead compounds. These results are hoped to advance the field of natural products research as potential therapeutic and curative AD agents.